Pemahaman tentang Ekaristi pada Siswa dan Siswi Kelas V dan VI di SD Katolik St. Antonius Wailan - Pangemanan, Stefhanus Hanny; Tore, Juan Marcelino (ECCE: Jurnal Pendidikan Pastoral Kateketik, 2024)
The focus of research in this thesis is Understanding the Eucharist in Students and Students of Grades V and VI at St. Antonius Wailan Catholic Elementary School. The focus is described in the formulation of the problem, namely: (a) How do students and students of Grades V and VI at St. Antonius Wailan Catholic Elementary School understand the Eucharist? (b) What are the factors that support and inhibit the students of Grades V and VI at St. Antonius Wailan Catholic Elementary School to understand the Eucharist? (c) What efforts can be made to make students in Grades V and VI at Wailan Catholic Elementary understand the Eucharist? The type of research used in the preparation of this thesis is descriptive research with a qualitative approach. Data collection techniques are carried out in three ways, namely: Observation, Interviews and Documentation Studies. In this study, the perpetrators and informants of the research were selected by the author using a purposive procedure, namely the determination of informants by selecting key persons who are in accordance with the criteria and problems of the research. The conclusion of this study consists of three parts. First: Students and students of Grades V and VI at St. Antonius Wailan Catholic Elementary School have understood quite well about the Eucharist as the source and peak of the faith of the people, because students and students of Grades V and VI understand that the Eucharist is a real supper of God and brings the grace of salvation and has a very important role in the life of the faithful. Second: The main supporting factor for students in grades V and VI at St. Anthony Wailan Catholic Elementary School in understanding the Eucharist is their involvement in liturgical duties in the church, the role of parents and teachers to support them in carrying out that task and their craft in following the Eucharist every week. Meanwhile, the inhibiting factors for students and students in grades V and VI at St. Antonius Wailan Catholic Elementary School in understanding the Eucharist are not focused on participating in the Eucharistic Celebration and lack of self-involvement in church tasks and lack of understanding of learning about the Eucharist at school because the language used is difficult to understand. Third: Efforts that can be made by students and students of Grades V and VI at Wailan Catholic Elementary School to understand the Eucharist, namely building their own intentions to be diligent in participating in the Eucharist and actively involved in it, participating in collection activities, catechesis or other faith development activities with the theme of the Eucharist and the role of parents to set an example, namely being faithful in Eucharistic activities.